HUBUNGAN SIKAP DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR EKONOMI SISWA SEKOLAH MENENGAH PERTAMA KELAS VII - Jacinta Karmila (JURNAL ELASTISITAS: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2019)
The research has the aims to describe the correlation of attitude, motivation and media for learning toward students’ achievement in Economics learning: (1) the correlation of attitude and students’ achievement in learning Economics; (2) the correlation of motivation with students’ achievement in learning Economics; (3) the correlation of attitude and motivation with sudents’ achievement in learning Economics. The number of students at social studies department of VIIth grade students at SMP Xaverius 2 Bandarlampung as many as 117 students were used as source material for data retrieval. Research data had taken by giving questionaires and tests to the students. Some techniques of data analysis used in the research are linear correlation and partial correlation. The conclusions of the research are: (1) attitude has a correlation with students’ achievement in learning Economics with linear correlation coefficient is 0.328 and partial correlation coefficient is 0.243; (2) motivation has a correlation with students’ achievement in learning Economics with linear coefficient correlation is 0.316 and partial correlation coefficient is 0.246; (3) attitude and motivaton have a correlation with students’ achievement in learning Economics with linear correlation coefficient is 0.324 and partial correlation coefficient is 0.238.